Meloidogyne enterolobii, a Major Threat to Tomato Production: Current Status and Future Prospects for Its Management - Philbrick, Ashley N.; Adhikari, Tika B.; Louws, Frank J.; Gorny, Adrienne M. (Frontiers in Plant Science, 2020)
The guava root-knot nematode, Meloidogyne enterolobii (Syn. M. mayaguensis), is an emerging pathogen to many crops in the world. This nematode can cause chlorosis, stunting, and reduce yields associated with the induction of many root galls on host plants. Recently, this pathogen has been considered as a global threat for tomato (Solanum lycopersicum L.) production due to the lack of known resistance in commercially accepted varieties and the aggressiveness of M. enterolobii. Both conventional morphological and molecular approaches have been used to identify M. enterolobii, an important first step in an integrated management. To combat root-knot nematodes, integrated disease management strategies such as crop rotation, field sanitation, biocontrol agents, fumigants, and resistant cultivars have been developed and successfully used in the past. However, the resistance in tomato varieties mediated by known Mi-genes does not control M. enterolobii. Here, we review the current knowledge on geographic distribution, host range, population biology, control measures, and proposed future strategies to improve M. enterolobii control in tomato.